ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA PADAMATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN KELAS X DI SMK NEGERI 4 KOTA JAMBI - Diliza Afrila, Dewi Purwita Sary, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the factors of student learning difficulties on the subjects of Workshop and Entrepreneurship class X in SMK Negeri 4 Kota Jambi. The type of this research is descriptive research with quantitative approach. The result of the research shows that (1) learning disability variables are in enough category with average 3,48 and Response Achievement Level (TCR) is 69,66 and (2) There are 12 (twelve) dominant factors influencing student learning difficulties, (b) Learning Motivation, (c) Learning Habits, (d) School Climate, (e) Teacher Competence, (f) Learning Resources, (g) Intelligence, (h) Interest in Learning, ( i) Socioeconomic Parents, (j) Peer Environment, (k) Learning Environment, and (l) Community Environment.Kata Kunci : Difficulty learning